2019
DOI: 10.1038/s41467-019-09954-9
|View full text |Cite
|
Sign up to set email alerts
|

Impaired cortico-striatal excitatory transmission triggers epilepsy

Abstract: STXBP1 and SCN2A gene mutations are observed in patients with epilepsies, although the circuit basis remains elusive. Here, we show that mice with haplodeficiency for these genes exhibit absence seizures with spike-and-wave discharges (SWDs) initiated by reduced cortical excitatory transmission into the striatum. Mice deficient for Stxbp1 or Scn2a in cortico-striatal but not cortico-thalamic neurons reproduce SWDs. In S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
97
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(109 citation statements)
references
References 66 publications
8
97
4
Order By: Relevance
“…These pharmacological and pharmaco-genetic results directly demonstrate a key role for the striatum in the control of absence seizures but are not supported by the lack of changes in the ictal firing of putative striatal fast-spiking and medium spiny neurons. Indeed, the latter result and other findings of Miyamoto et al (2019) are in contrast with previous observations in morphological identified striatal neurons of GAERS rats (see above) ( Fig. 6 ) ( Slaght et al , 2004 ).…”
Section: Introductioncontrasting
confidence: 99%
See 1 more Smart Citation
“…These pharmacological and pharmaco-genetic results directly demonstrate a key role for the striatum in the control of absence seizures but are not supported by the lack of changes in the ictal firing of putative striatal fast-spiking and medium spiny neurons. Indeed, the latter result and other findings of Miyamoto et al (2019) are in contrast with previous observations in morphological identified striatal neurons of GAERS rats (see above) ( Fig. 6 ) ( Slaght et al , 2004 ).…”
Section: Introductioncontrasting
confidence: 99%
“…A recent study on STXBP1 , a gene encoding the presynaptic protein Munc18-1, shows that injection of muscimol in the striatum of Stxbp1 −/− mice blocks their short (0.5–2 s) ethosuximide-sensitive absence seizures ( Miyamoto et al , 2019 ). Moreover, striatal application of NASPM, a selective blocker of calcium-permeable AMPA receptors, which are more abundant in the fast-spiking striatal interneurons than in the striatal medium spiny neurons ( Deng et al , 2007 ), elicits absence seizures in wild-type mice and (continuous) activation of Designer Receptor Exclusively Activated by Designer Drugs (DREADDS)-transfected fast-spiking striatal interneurons markedly reduces ASs in Stxbp +/− mice ( Miyamoto et al , 2019 ). These pharmacological and pharmaco-genetic results directly demonstrate a key role for the striatum in the control of absence seizures but are not supported by the lack of changes in the ictal firing of putative striatal fast-spiking and medium spiny neurons.…”
Section: Introductionmentioning
confidence: 99%
“…Our results, in combination with these studies, suggest that the PO, and perhaps other thalamic or sub-cortical structures, may cascade the thalamocortical network into a pathological state. The long-lasting PiP that we identified may be the trigger itself, or may reflect a process that arises from other brain regions such as the striatum 87 . In any case, the distinct pre-seizure activity, if causative, must engage the larger thalamocortical network, and the mechanisms of this engagement will be the subject of future studies.…”
Section: Thalamic Pre-ictal Peak As a Marker Of Pathological Neural Smentioning
confidence: 91%
“…Nevertheless, Scn2a haploinsufficient mouse models (Scn2a +/− ) show significant phenotypes linked to human disease and have been used to further elucidate the role of Na V 1.2 in both normal neurodevelopment and disease. Scn2a +/− mice display mild absence-like seizures, delayed spatial learning, increased contextual fear learning, impaired fear extinction, and hyperactivity [42,46,75,76], all of which may be related to ASD symptoms in humans. Cortical neurons from these mice display impaired excitability and impaired excitatory synapse function [61].…”
Section: Haploinsufficient Mouse Modelsmentioning
confidence: 99%